Mapping of QTLs for Yield Traits Using F2:3:4 Populations Derived From Two Alien Introgression Lines Reveals qTGW8.1 as a Consistent QTL for Grain Weight From Oryza nivara - Beerelli, Kavitha; Balakrishnan, Divya; Addanki, Krishnam Raju; Surapaneni, Malathi; Rao Yadavalli, Venkateswara; Neelamraju, Sarla (Frontiers in Plant Science, 2022)
Wild introgressions play a crucial role in crop improvement by transferring important novel alleles and broadening allelic diversity of cultivated germplasm. In this study, two stable backcross alien introgression lines 166s and 14s derived from Swarna / Oryza nivara IRGC81848 were used as parents to generate populations to map quantitative trait loci for yield related traits. Field evaluation of yield related traits in F2, F3 and F4 population was carried out in normal irrigated conditions during wet season 2015, dry seasons 2016 and 2018 respectively. Plant height, tiller number, productive tiller number, total dry matter and harvest index showed highly significant association to single plant yield in F2, F3 and F4. In all, 21, 30 and 17 quantitative trait loci (QTLs) were identified in F2, F2:3 and F2:4 respectively for yield related traits. QTLs qPH6.1 with 12.54% PV in F2, qPH1.1 with 13.01% PV and qTN6.1 with 10.08% PV in F2:3 and qTGW6.1 with 15.19% PV in F2:4 were identified as major effect QTLs. QTLs qSPY4.1 and qSPY6.1 were detected for grain yield in F2 and F2:3 with PV 8.5% and 6.7% respectively. The trait enhancing alleles of QTLs qSPY4.1, qSPY6.1, qPH1.1, qTGW6.1, qTGW8.1, qGN4.1 and qTDM5.1 were from O. nivara. QTLs of the yield contributing traits were found clustered in the same chromosomal region. qTGW8.1 was identified in a 2.6Mb region between RM3480 and RM3452 in all three generations with PV 6.1 to 9.8%. This stable and consistent qTGW8.1 allele from O. nivara can be fine mapped for identification of causal genes. From this population, lines C212, C2124, C2128 and C2143 were identified with significantly higher SPY and C2103, C2116 and C2117 had higher thousand grain weight values than both the parents and Swarna consistently across the generations and are useful in gene discovery for target traits and further crop improvement.